Neuroparenting Perspektif Buya Hamka dalam Tafsir Al-Azhar - Syifa’ Nadia Rizka; Ali Nurdin; Ikhlas Budiman (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze how neuroparenting principles can be enriched through Qur'anic parenting values ​​based on Hamka's Tafsir Al-Azhar. This study uses the thematic interpretation method (*tafsir maudhu'i*) with a qualitative approach. Primary data consists of Qur'anic verses related to childcare and Tafsir Al-Azhar as the main source of interpretation, while secondary data are obtained from books, journal articles, and scientific literature discussing neuroparenting, neuroscience, Islamic education, and childcare. Data collection is carried out through documentation studies by tracing, identifying, and inventorying verses and literature relevant to the research theme. Data analysis is carried out through the stages of data reduction, theme categorization, interpretation of verses based on Tafsir Al-Azhar, and comparative analysis with the concept of neuroparenting in modern neuroscience studies. The results of the study indicate that the concept of neuroparenting in the Qur'an as interpreted by Hamka emphasizes the balance between the development of reason, heart, and faith in the formation of a child's personality. Hamka views parenting as an educational process encompassing cognitive, emotional, spiritual, and moral aspects, grounded in monotheism, compassion, wisdom, and exemplary behavior. These findings demonstrate a strong relevance between modern neuroparenting principles and Quranic parenting values. This research contributes to the development of a Quranic neuroparenting paradigm that integrates scientific and spiritual approaches as a foundation for holistic childcare in the modern era.